Semantic Representations of Bioethics by Young University Students From the Ethics of Care - Cantú Martínez, Pedro César (2023)
Introduction: At present, gender studies are very important, so research is carried out that will allow us to know the discernment of women about bioethics. Objective: To recognize the semantic representations that young university students have in relation to bioethics. Methodology: This study was carried out in university students in the area of biological sciences. The technique of natural semantic networks and the posture of ethics of care were used for its examination. Results: 191 words were evaluated, representing a richness of 81 statements. The main expressions were “trust”, “dialogue”, “debate”, “duty” and “principles”. Discussion: College students exercise their practical reason by choosing what is best for others, confirming the assumptions of the ethics of care.